Influence of interlimb lean muscle mass asymmetry on countermovement jump neuromuscular performance qualities among American football players - Polletta, J.; Leung, K.; Diaz, D.; Branum, N.; Mokha, M. (The Journal of Strength and Conditioning Research, 2025)
Body composition is a determinant of athletic performance. The purpose of this study was to determine the influence of lower limb lean muscle mass (LMM) asymmetry on countermovement jump (CMJ) performance and kinetic asymmetry during both eccentric and concentric CMJ phases. Seventy-four American football players (age, 23.0 ± 0.9 years; height, 1.86 ± 0.07 m; mass, 104.9 ± 21.6 kg; lean body mass, 88.7 ± 12.5 kg) training for the 2024 National Football League draft underwent body composition assessment using an InBody 270 bioelectrical impedance analyzer that yielded right and left leg LMM in kg. Subjects then performed 3 CMJs on dual uniaxial force plates that allowed for the calculation of jump height (JH), reactive strength index modified (RSImod), and interlimb percentage asymmetry of peak force and impulse for eccentric and concentric phases. A paired t-test and Pearson Product-moment Correlation Coefficients calculated the difference between left and right LMM and the associations between the symmetry variables, respectively, p = 0.05. Right and left leg LMM were significantly different (t(73) = 3.772, p = 0.001). However, no significant relationships were found between lower limb LMM asymmetry (0.67 ± 0.67%) and any asymmetry in CMJ eccentric peak force (4.77 ± 3.75%), r(72) = 0.001, p = 0.954; eccentric deceleration impulse (5.23 ± 4.36%), r(72) = 0.158, p = 0.180; concentric peak force (2.99 ± 2.54%), r(72) = -0.70, p = 0.553; concentric impulse (3.06 ± 2.97%), r(72) = 111, p = 0.347; JH (41.8 ± 7.3 cm), r(72) = -0.205, p = 0.08; or RSImod (0.53 ± 0.14 m·s-1), r(72) = -0.151, p = 0.199. The magnitude of LMM asymmetry did not influence CMJ performance or asymmetry magnitude. Reducing CMJ kinetic asymmetry may require targeted programming, especially for the eccentric loading phase.